Steps towards Knowledge (2008)
In 2007, the hotbeds of research for school students were created by EAFIT Children's University as a formative research strategy open to all alumni of the program, so that they continue taking steps towards knowledge. The project led by the Directorate of Research and Teaching and the Department of Communication and Culture seeks to encourage curiosity, love for knowledge and creativity.